Choice and Uncertainty in Robert Frost’s The Road Not Taken: A Thematic Analysis - Bhattarai, Rajendra (International Research Journal of MMC, 2025)
The main focus of this article is to identify choice and uncertainty as the primary themes in Robert Frost's poem The Road Not Taken. The research utilized terminology or phrases as codes that added to the themes of decision-making and lack of clarity. The main information for this research came from the poem, while additional information was gathered from books, academic articles, and online resources. The study found that expressions or codes like "diverged", "sorry I could not travel both", "traveler", "just as fair", "perhaps the better claim", and "less traveled by" highlighted the theme of choice, while assertions, such as "long I stood", "looked down one as far as I could", "I doubted", and "made all the difference" emphasized the theme of uncertainty. The research adds to current literary analysis by exploring themes in The Road Not Taken, supporting theories that see the poem as representative of human uncertainty and the attraction of unknown possibilities. It indicates that thematic analysis can reveal patterns in literary works to enhance comprehension of literary categories. This article is important for individuals interested in teaching and analyzing literary works.